Monitoring of underground water: Necessary step in determining the method for site remediation - Knudsen Tatjana Šolević; Miroslav Vrvić; Dejan Nešković (Zaštita Materijala)
The object of this study was to investigate the quality of underground water on the location of heating plant 'Novi Beograd' (Serbia). The examination included a system of 10 piezometers (P1, P5, P6, P7, P8, P9, P10, P11, P12, P13), which are constructed in two cycles (P1, P5, P6 and P13 are located at depth of up to 10 m, and P7 to P12 are located at depth of up to 15 m). Obtained results indicate that the area P5 to P8, as well as P12 and P13, has a concentration of total petroleum hydrocarbons greater that the remediation value standardized as 0,6 mg/L. It was also determined that the total volume of the contaminated underground water is around 105.000m3. All of the above indicates that it is necessary to start the remediation of underground water contaminated with petroleum hydrocarbons and that the most appropriate remediation procedure for this site is in situ bioremediation.